1975
DOI: 10.1007/bf00453706
|View full text |Cite
|
Sign up to set email alerts
|

Neue morphologische Grundlagen zur Physiologie des Riechens und Schmeckens

Abstract: New results as revealed by scanning and transmission electron microscopy have given us further knowledge about the structure of the olfactory region of vertebrates. With comparative studies we are now able to discuss the functional relationship of this region. In all vertebrates the olfactory cell is a primary sensory cell. The apical segment of the olfactory cell with its olfactory vesicle is involved in the formation of the olfactory border. As a rule of the receptor possesses cilia or cilia-like processes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1979
1979
1997
1997

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…There are five cell types: (1) ciliated sensory neurons, (2) microvillar sensory neurons, (3) microvillar supporting cells, (4) goblet cells, and (5) basal cells. The two types of sensory neurons have been reported in other teleosts (Bannister, 1965;Schulte, 1972;Bertmar, 1973;Andres, 1975;Ichikawa and Ueda, 1977). In addition, a third sensory neuron type possessing a single rod-shaped appendage has been reported in some teleosts (Bannister, 1965;Wilson and Westerman, 1967;Schulte, 1972;Bertmar, 1973), but it is unclear whether or not this is a sensory neuron (Andres, 1975;Ichikawa and Ueda, 1977) or perhaps even an artifact of fixation (Eller et al, 1985).…”
Section: Discussionmentioning
confidence: 98%
“…There are five cell types: (1) ciliated sensory neurons, (2) microvillar sensory neurons, (3) microvillar supporting cells, (4) goblet cells, and (5) basal cells. The two types of sensory neurons have been reported in other teleosts (Bannister, 1965;Schulte, 1972;Bertmar, 1973;Andres, 1975;Ichikawa and Ueda, 1977). In addition, a third sensory neuron type possessing a single rod-shaped appendage has been reported in some teleosts (Bannister, 1965;Wilson and Westerman, 1967;Schulte, 1972;Bertmar, 1973), but it is unclear whether or not this is a sensory neuron (Andres, 1975;Ichikawa and Ueda, 1977) or perhaps even an artifact of fixation (Eller et al, 1985).…”
Section: Discussionmentioning
confidence: 98%
“…The mucus consisted of two zones (Andres, 1969;Muller et al, 1979): an outer zone, including the terminal film, in which the distal segments of the olfactory receptor cilia were located; and an inner zone, which covered the proximal ciliary segments, the microvilli of the sustentacular cells, and the apical surfaces of the epithelial cells. The outer zone appeared to be composed of fine filaments; a marked similarity in appearance between the outer zone and the secretory material in Bowman's glands was noted in birds and mammals (Andres, 1966(Andres, , 1969(Andres, , 1975Seifert, 1971;Muller et al, 1979). The inner zone was composed of a lighter-appearing filamentous material.…”
Section: Olfactory Mucusmentioning
confidence: 92%
“…Patches of respiratory mucosa were reported to occur among areas of olfactory mucosa (Andres, 1975;Nakashima et al, 1984;Nakashima et al, 1985). In light microscopic studies of human olfactory mucosa from our laboratory, using immunohistochemistry to localize olfactory marker protein for identifying olfactory mucosa unequivocally, we observed that the type of respiratory epithelium most commonly found adjacent to olfactory mucosa contained tall columnar ciliated cells; frequently, invaginations of this type of epithelium formed "glands" in the lamina propria (Getchell and Mellert, 1991).…”
Section: Bowman's Glandsmentioning
confidence: 93%
“…At least a few glomeruli in Periplaneta are innervated by both uPNs and mPNs (Kraus, 1991). Interestingly, uniglomerular PNs prevail in the mammalian olfactory bulb, where the primary dendrites of about a dozen mitral cells are found per glomerulus, but in fish, projection neurons are often pluriglomerular (Andres, 1975); however, mPNs like those found in insects have not been described in vertebrates.…”
Section: Neurons In the Antenna1mentioning
confidence: 99%